EKSPERIMEN PENGGUNAAN BIJI PLASTIK ABS (ACRYLONITRILE BUTADIENE STYRENE) SEBAGAI BAHAN TAMBAHAN CAMPURAN ASPAL PORUS - Didakus Thomas Dapa Ole; M. Sa'dillah; Blima Oktaviastuti (Journal Innovation of Civil Engineering (JICE), 2023)
Increasing the strength of the porous asphalt mixture in the field of road contraction, in this context, porous asphalt is often used as road pavement. ABS plastic pellets (Acrylonitrile Butadiene Styrene) have the same properties as asphalt, namely, thermoplastic has a penetration value equivalent to asphalt pen 60/70, plays an important role in road pavement adhesives as an alternative and has high strength and is resistant to deformation itself. The objective of the experiment was to determine the characteristics of Marshall on optimum asphalt content (KAO) and the effect of adding ABS plastic pellets on the performance of porous asphalt was reviewed based on the Marshall test, Cantabro Loss and Asphalt Flow Down. The research used experimental testing methods in the laboratory. The research was conducted with asphalt pen content of 60/70, namely 4%, 4.5%, 5%, 5.5% 6% and additional levels of ABS plastic pellets 0%, 2%, 4%, 6% and 8%. From the planned grade for the addition of ABS plastic pellets mentioned above, the optimum bitumen content is obtained, namely 6% with a VIM value at 6% content of 23.61%, for a VMA value of 27.20%, for a stability value of 924.95 kg and the flow value obtained was 3.23 mm while the MQ value was 311.15 kg/mm. with standard or parameters namely AAPA 2004(Australian Asphalt Pavement Association).